2012
DOI: 10.1103/physreva.85.033625
|View full text |Cite
|
Sign up to set email alerts
|

Sauter-Schwinger-like tunneling in tilted Bose-Hubbard lattices in the Mott phase

Abstract: We study the Mott phase of the Bose-Hubbard model on a tilted lattice. On the (Gutzwiller) mean-field level, the tilt has no effect -but quantum fluctuations entail particle-hole pair creation via tunneling. For small potential gradients (long-wavelength limit), we derive a quantitative analogy to the Sauter-Schwinger effect, i.e., electron-positron pair creation out of the vacuum by an electric field. For large tilts, we obtain resonant tunneling related to Bloch oscillations. Introduction. There are many str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 52 publications
1
42
0
Order By: Relevance
“…It was found that the results are in good agreement with rigorous high-temperature and low-temperature expansions [36]. A related approximation method was previously applied to investigate the dynamics of lattice site correlations after a quantum quench [39][40][41] and particlehole pair creation in tilted optical lattices [42]. The 1/Zexpansion is valid for all values of the interaction energy and the hopping energy.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…It was found that the results are in good agreement with rigorous high-temperature and low-temperature expansions [36]. A related approximation method was previously applied to investigate the dynamics of lattice site correlations after a quantum quench [39][40][41] and particlehole pair creation in tilted optical lattices [42]. The 1/Zexpansion is valid for all values of the interaction energy and the hopping energy.…”
Section: Introductionsupporting
confidence: 61%
“…From the partition function we obtained local quantities such as the on-site probabilities p n as well as the non-local thermal correlations b † µbν . It should be noted that, in the limit of vanishing temperature, the correlation functions b † µbν as well as the occupation probabilities can also be obtained from 1/Zhierarchy that describes the dynamics of lattice site correlations [39,42]. …”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach was recently suggested in Refs. [401,404,405,511] which deals with the dynamical equations for the reduced density matrices of different number of lattice sites. However, the full theoretical description of sufficiently large systems in the whole parameter range and for arbitrarily long times is still not reached.…”
Section: Discussionmentioning
confidence: 99%
“…In such a description, excitations in the Bragg process are created as particle-hole pairs [383,401,402]. However, the latter appears to be of the second order in the inverse of coordination number Z = 2d [401,[403][404][405] and, therefore, is not taken into account by the standard Gutzwiller ansatz.…”
Section: Bragg Scatteringmentioning
confidence: 99%
“…The results (86), (87), and (91) can also be obtained via other approaches, such as the spin density wave ansatz [101] (which is related to dynamical mean field theory according to Ref. [102]).…”
Section: B Quantum Depletionmentioning
confidence: 99%